RESISTANCE TO THE BLAST AGENT AND THE MORPHOBIOLOGICALFEATURES OF GENOTYPES IN THE Oryza sativa L. COLLECTION FROM VARIOUS ECOLOGICAL AND GEOGRAPHICAL GROUPS IN CONDITIONS OF КUBAN ZONE OF RICE GROWING - T. L. Korotenko; O. A. Bragina; I. I. Suprun; Zh. M. Mukhina; Yu. V. Epifanovich; A. A. Petrukhnenko; T. А. Khorina (Вавиловский журнал генетики и селекции, 2018)
The most common and harmful disease of the agricultural crop rice is a “burn” caused by the fungus Magnoporthe grisea (Hebert) Barr, the causative agent of rice blast. The important direction of modern domestic rice breeding is the development of high-yielding varieties resistant to blast. To solve the problem, it is important to search for sources and donors of resistance to the Krasnodar population of the pathogen among ecotypes of different ecological and geographical origin. Evaluation of the rice collection diversity for resistance to blast was carried out both on a natural background and on an infectious-provocative one. Immunological evaluation and phenotyping were carried out in 2015–2017 on 154 varieties of the Oryza sativa L. species from 7 ecological and geographical cultivation zones. Over the years of research, the range of variation in the intensity of the disease development in varieties was in the range from 1.1 to 77.8 %. The differences in the resistance of rice varieties to the pathogen between ecological groups and countries have been found. Most of the studied samples have shown medium resistance, there were isolated 51 resistant forms. Most often stable forms were found among the germplasm from China, Italy, the Philippines and Korea, and the unstable ones were from African countries, Japan, Primorye and Vietnam. Introduced samples resistant to the disease were identified and adapted to soil and climatic conditions and rice cultivation technologies of the Kuban, they were included in the breeding scheme for developing pathogen-resistant rice varieties with the extension of their genetic basis. The article presents data on the variation of morphological traits and the rate of development of plants of international varieties from 24 countries in the conditions of the south of Russia. The results of the comparison of germplasm of domestic and foreign varieties according to the degree of resistance to the pathogen in conditions of natural infection in the field experiment for five years are presented. As a result of the evaluation of plant resistance to the Krasnodar population of the pathogen, the effective genes for resistance to the pathogen for breeding programs of the south of Russia and the molecular genetic analysis of the rice collection variety were determined: Pi-1, Pi-z, Pi-ta, Pi-z5, Pi-9, Pi-5(t), Pi-t, Pi-19.